Fundamentals of Clinical Data Science 2018
DOI: 10.1007/978-3-319-99713-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Data Sources

Abstract: Electronic medical records (EMRs), often also referred to as electronic health records (EHRs), are a major source of clinical data (although EMR and EHR have subtle differences). ("EHR (electronic health record) vs. EMR (electronic medical record)," [6]) EMRs are computerized medical information systems that collect, store and display patient information. They are means to create legible and organized recordings and to access clinical information about individual patients. EMRs have been described as an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…The most common barriers to data acquisition are 25 : Technical barriers (lack of interoperability). Political barriers (lack of effective data-sharing policies). Ethical barriers (lack of consensus on privacy and confidentiality). Administrative barriers (inadequate human resources to handle clinical data). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common barriers to data acquisition are 25 : Technical barriers (lack of interoperability). Political barriers (lack of effective data-sharing policies). Ethical barriers (lack of consensus on privacy and confidentiality). Administrative barriers (inadequate human resources to handle clinical data). …”
Section: Discussionmentioning
confidence: 99%
“…The most common barriers to data acquisition are 25 : Technical barriers (lack of interoperability). Political barriers (lack of effective data-sharing policies).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies in our scoping review (17/30) described step 3 (prospective validation) of the validation strategy of Scheepers‐Hoeks et al 13 , 14 We reviewed clinical validation studies and therefore step 1 (technical CDSS validation) of the strategy was not within the scope of our review. None of the included studies reported all steps (2, 3 and 4) of the validation strategy and none referred to a published CDSS validation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…12 A medication‐related CDSS validation strategy consists of four steps: (1) technical validation to check whether the CDSS functions as expected, (2) retrospective validation to review whether the output is clinically relevant, actionable and useful, (3) prospective validation before implementation in a real‐life EHR to check whether the CDSS fits in the workflow (e.g., timing and frequency), and finally (4) post‐implementation validation for continuous improvement. 13 , 14 The validation process can prevent irrelevant output for the clinical setting, alert fatigue or low user acceptance. Validation of a CDSS is, therefore, key for successful implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation